2022
DOI: 10.3389/fimmu.2022.919408
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Waning of Protection With Different SARS-CoV-2 Primary and Booster Vaccines During the Delta Pandemic Wave in 2021 in Hungary (HUN-VE 3 Study)

Abstract: BackgroundIn late 2021, the pandemic wave was dominated by the Delta SARS-CoV-2 variant in Hungary. Booster vaccines were offered for the vulnerable population starting from August 2021.MethodsThe nationwide HUN-VE 3 study examined the effectiveness and durability of primary immunization and single booster vaccinations in the prevention of SARS-CoV-2 infection, Covid-19 related hospitalization and mortality during the Delta wave, compared to an unvaccinated control population without prior SARS-CoV-2 infection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 31 publications
5
47
0
2
Order By: Relevance
“…As in our study, a booster dose was required to restore neutralizing activity against Delta in COVID-19 naïve vaccine recipients. These data are confirmed by real word data from two independent studies that show that vaccine efficacy against infection with the Delta variant was around 80% soon after primary vaccination (<120 days), while it decreased over time to 0-50% (>120 days) (43,44). In both studies, vaccine efficacy against infection with the Delta variant was restored by the booster dose.…”
Section: Resultssupporting
confidence: 68%
“…As in our study, a booster dose was required to restore neutralizing activity against Delta in COVID-19 naïve vaccine recipients. These data are confirmed by real word data from two independent studies that show that vaccine efficacy against infection with the Delta variant was around 80% soon after primary vaccination (<120 days), while it decreased over time to 0-50% (>120 days) (43,44). In both studies, vaccine efficacy against infection with the Delta variant was restored by the booster dose.…”
Section: Resultssupporting
confidence: 68%
“…Indeed, lower VE against the Delta variant compared to the Alpha [ 20 , 21 ] variant, and the waning of VE over time have both been widely reported. Waning effectiveness of protection against SARS-CoV-2 infection was shown in another Hungarian study in the same nation-wide setting, especially six months after primary immunization [ 22 ], as well as in a similar nation-wide study from Greece [ 23 ]; this study also reported very high VE (>90%) in all age groups for BNT162b2 and ChAdOx1 against severe disease (requiring intubation) and death, but it did not examine VE against laboratory-confirmed COVID-19 cases. The data on the effectiveness of BBiBP-CorV are less abundant.…”
Section: Discussionmentioning
confidence: 96%
“…A HUN-VE 3 a 2021 őszi járványhullám alatti vakcinahatékonyságot vizsgálta az akkor domináns delta-variáns ellen, és arra jutott, hogy bár az oltás beadása után idővel minden vakcina hatékonysága csökkent, de szinte minden tekintetben a kínai Sinopharm-oltás nyújtotta a legalacsonyabb védelmet. Az eredmények kiemelték azt is, hogy a kínai vakcina emlékeztető oltásként adva is sokkal kevésbé vált be, mint a többi, itthon használt vakcina (Vokó et al 2022). Vokó és szerzőtársai tanulmányukban bemutatták, hogy a vakcinahatékonyság minden vakcinatípus esetében csökkent a negyedik hullám során, és megerősítette az emlékeztető oltások kiemelkedő hasznát az mRNS-vakcinákkal vagy a Janssen oltásával összefüggésben.…”
Section: Járványkezelés Magyarországon -"Húzd Meg Ereszd El"unclassified
“…Vokó és szerzőtársai tanulmányukban bemutatták, hogy a vakcinahatékonyság minden vakcinatípus esetében csökkent a negyedik hullám során, és megerősítette az emlékeztető oltások kiemelkedő hasznát az mRNS-vakcinákkal vagy a Janssen oltásával összefüggésben. A halálozás elleni védelem a következőképpen alakult az egyes vakcinatípusoknál: Pfizer/BioNTech: a 65 év felettiek körében 82% (65 év alattiaknál 87%); Moderna: 93% (78%); Szputnyik V: 86% (89%); AstraZeneca: 85% (90%); Sinopharm: 59% (67%); Janssen: 54% (60%) (Vokó et al 2022).…”
Section: Járványkezelés Magyarországon -"Húzd Meg Ereszd El"unclassified